2023
DOI: 10.1371/journal.pone.0291915
|View full text |Cite
|
Sign up to set email alerts
|

2-iminobiotin, a selective inhibitor of nitric oxide synthase, improves memory and learning in a rat model after four vessel occlusion, mimicking cardiac arrest

Cacha Peeters-Scholte,
Sigal Meilin,
Yafit Berckovich
et al.

Abstract: Survivors of out-of-hospital cardiac arrest (OHCA) experience between 30% and 50% cognitive deficits several years post-discharge. Especially spatial memory is affected due to ischemia-induced neuronal damage in the hippocampus. Aim of this study was to investigate the potential neuroprotective effect of 2-iminobiotin (2-IB), a biotin analogue, on memory and learning in a four-vessel occlusion model of global ischemia using the Water Maze test. Sprague-Dawley rats were randomly assigned to either sham operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…After cardiac arrest, neuronal death is observed in the hippocampus, cerebral cortex, basal ganglia, thalamus, and amygdala, structures responsible for memory, as well as general brain atrophy and, ultimately, progressive dementia of Alzheimer's disease phenotype (Figure 1) [51,52,59,77]. One proposal explaining the above changes suggests that long non-coding RNA increases the expression of the adapter protein ShcA in the hippocampus, which causes cognitive impairment after cardiac arrest as a result of neuroinflammation and apoptosis of pyramidal neurons [112][113][114].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After cardiac arrest, neuronal death is observed in the hippocampus, cerebral cortex, basal ganglia, thalamus, and amygdala, structures responsible for memory, as well as general brain atrophy and, ultimately, progressive dementia of Alzheimer's disease phenotype (Figure 1) [51,52,59,77]. One proposal explaining the above changes suggests that long non-coding RNA increases the expression of the adapter protein ShcA in the hippocampus, which causes cognitive impairment after cardiac arrest as a result of neuroinflammation and apoptosis of pyramidal neurons [112][113][114].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive functions depend on complex interactions between cortical and subcortical areas through various brain networks (Figure 1) [13]. Cognitive problems develop in 42-50% of patients who survive cardiac arrest up to several years after discharge from hospital [13,59]. Other studies have reported that in people who survived cardiac arrest, 50-100% of them experienced cognitive, mood, and functioning disorders [6,7,60].…”
Section: Cognitive Deficits After Cardiac Arrestmentioning
confidence: 99%
See 1 more Smart Citation